Protocol for participatory on-farm experiment for rice field fisheries/rice field pond - Sean, Vichet; Freed, Sarah; Sithirith, Mak; Tuy, Sinak; Sun, Vathanak; Ouk, Hak; Kong, Sovannara (WorldFish, 2023)
Cambodia’s rain-fed and flooded rice fields are important and productive sources of inland fish and other aquatic animals, including frogs and snails. These aquatic resources are important to millions of Cambodians, particularly those in rural areas. They make important contributions to rural livelihoods, to food security, climate change, nutrition and income generation. Through their roles in protecting wild fish during dry periods and providing good habitats for fish to breed, spawn and grow, CFRs maintain and increase fish numbers in the surrounding rice fields. FiA has supported the establishment of 183 CFRs in the Mekong Delta, which have increased the production of rice field fisheries. The purposes of this rice-field pond experiment are: • To identify the fish yield, income and nutrient for rural people; • To introduce and demonstrate the technologies adapted climate resilience to increase productivities of fisheries and paddy yield. • To identify the survival rate and weight gain of fish stocked after brooding fish during dry season.